(3GdcGaj aj UfGYI GdWHs - (3YOfGf GdYjf RQHj , ehab GdOjf CHh fUQ,J (B548 (3g` s ((3fhQ GdSjQai s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ZQV ef gPG GdcJGH JMbjb GdaVdGA HYedi ef GdWH Ydi ChLR eG jJgjC Cf jecfg ef JYQja CSHGH GdYdd hCYQGVgG s
(3BNQgG (B:s
(3aEPG CUHM TQH eGA fbY CaSJjf bHd GdWYGe , aEfg jOaYg GdNeGQ JeJ cJGH GdcGai ai GdWH s
(3eUOQI HagQS eaUd GdehVhYGJ GdcJGHs
(3hGfXQ faS GdfSNI HQbe (B197 " (3GdcGai ai GdWH (B"s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B273s
Keywords: (3GdWHs